Polymer electrolyte glue : a universal interfacial modification strategy for all-solid-state Li batteries - Dong, Derui (2020)
In recent years solid Li+ conductors with competitive ionic conductivity to those of liquid electrolytes have been reported. However, the incorporation of highly conductive solid electrolytes into the lithium-ion batteries is still very challenging mainly due to the high resistance existing at the solid-solid interfaces throughout the battery structure. Here, we demonstrated a universal interfacial modification strategy through coating a curable polymer-based glue electrolyte between the electrolyte and electrodes, aiming to address the poor solid-solid contact and thus decrease high interfacial resistance. The liquid glue exhibits both great wettability as well as chemical/electrochemical stability to most of the electrodes, and it can be easily solidified into a polymer electrolyte layer through a "post-curing" treatment. As a result, symmetric Li batteries with the glue modification exhibit much smaller impedance and enhanced stability upon plating/stripping cycles compared to the batteries without glue modification. The all-solid-state Li-S batteries with glue modification show significantly enhanced performances. The strategy of developing glue electrolytes to improve the electrode-electrolyte interface contact provides an alternative option for improving many other solid-state batteries.